Oxford Textbook of Oncology - Kerr, D. J. David J; Haller, D. G. Daniel G; van de Velde, C. J. H. Cornelis J. H; Baumann, M. Michael (Oxford University Press, 2018)
Written and edited by internationally recognised leaders in the field, the new edition of the Oxford Textbook of Oncology has been fully revised and updated, taking into consideration the advancements in each of the major therapeutic areas, and representing the multidisciplinary management of cancer. Structured in six sections, the book provides an accessible scientific basis to the key topics of oncology, examining how cancer cells grow and function, as well as discussing the aetiology of cancer, and the general principles governing modern approaches to oncology treatment. The book examines the challenges presented by the treatment of cancer on a larger scale within population groups, and the importance of recognising and supporting the needs of individual patients, both during and after treatment. A series of disease-oriented, case-based chapters, ranging from acute leukaemia to colon cancer, highlight the various approaches available for managing the cancer patient, including the translational application of cancer science in order to personalise treatment. The advice imparted in these cases has relevance worldwide, and reflects a modern approach to cancer care. The Oxford Textbook of Oncology provides a comprehensive account of the multiple aspects of best practice in the discipline, making it an indispensable resource for oncologists of all levels of training and practice.